Where There's a Will There's a Way: Marley v Rawlings and Another. Issue 1 (January 2015) - Goodwin, James; Granger, Edward
<x xml:space="preserve">Abstract</x> In Marley v Rawlings and another, a unanimous Supreme Court has widened the scope of judicial power to rectify a will under section 20 of the Administration of Justice Act 1982. An intended will that falls foul of formality requirements may now have such defects resolved by rectification, and the meaning of 'clerical error' – one of the two possible bases for invoking the rectification doctrine – has been expanded. The Court's decision to resolve the issue by this method rather than by recourse to the doctrine of construction may prove to have implications for the extended scope of the latter. Moreover, the recent award of a third party costs order in this case is also likely to have a significant impact on the manner in which similar disputes are conducted in the future.